Editorial Perspective: How can we help the children of Ukraine and others affected by military conflict?. Issue 3 (26th July 2022) - Calam, Rachel; El‐Khani, Aala; Maalouf, Wadih
Abstract : Parents and caregivers play a key role in protecting children from the stresses of war. Their own experiences, changes they see in children in their care and the nature of the parenting they provide can have a profound effect on childrens' reactions. The adoption of a pyramid of resources from universally available psychoeducational materials to specialised forms of trauma‐informed interventions allows for screening and provision of appropriate levels of assistance. The importance of consideration of the family's context, the evidence base and the capacity of informal and professional networks to support caregiving is discussed. Resources available through the United Nations Office on Drugs and Crime are provided to share experiences of building a pyramid of interlinked, evidence‐based, trauma‐informed interventions which have been developed in collaboration with families and practitioners experiencing life through the contexts of military conflict, displacement and resettlement.